Nociceptive Neurons Differentially Express Fast and Slow T-Type Ca2+ Currents in Different Types of Diabetic Neuropathy - Eugen V. Khomula; Anya L. Borisyuk; Viacheslav Y. Viatchenko-Karpinski; Andrea Briede; Pavel V. Belan; Nana V. Voitenko (Neural Plasticity)
T-type Ca2+ channels are known as important participants of nociception and their remodeling contributes to diabetes-induced alterations of pain sensation. In this work we have established that about 30% of rat nonpeptidergic thermal C-type nociceptive (NTCN) neurons of segments L4–L6 express a slow T-type Ca2+ current (T-current) while a fast T-current is expressed in the other 70% of these neurons. Streptozotocin-induced diabetes in young rats resulted in thermal hyperalgesia, hypoalgesia, or normalgesia 5-6 weeks after the induction. Our results show that NTCN neurons obtained from hyperalgesic animals do not express the slow T-current. Meanwhile, the fraction of neurons expressing the slow T-current did not significantly change in the hypo- and normalgesic diabetic groups. Moreover, the peak current density of fast T-current was significantly increased only in the neurons of hyperalgesic group. In contrast, the peak current density of slow T-current was significantly decreased in the hypo- and normalgesic groups. Experimental diabetes also resulted in a depolarizing shift of steady-state inactivation of fast T-current in the hyperalgesic group and slow T-current in the hypo- and normalgesic groups. We suggest that the observed changes may contribute to expression of different types of peripheral diabetic neuropathy occurring during the development of diabetes mellitus.